Particle-size dependent effects in the Balb/c murine model of inhalational melioidosis - Thomas, Richard; Davies, Carwyn; Nunez, Alejandro; Hibbs, Stephen; Eastaugh, Lin; Harding, Sarah; Jordan, Janine; Barnes, Kay; Oyston, Petra; Eley, Steve (Frontiers in Cellular and Infection Microbiology, 2012)
Deposition of Burkholderia pseudomallei within either the lungs or nasal passages of the Balb/c murine model resulted in different infection kinetics. The infection resulting from the inhalation of B. pseudomallei within a 12 μm particle aerosol was prolonged compared to a 1 μm particle aerosol with a mean time-to-death (MTD) of 174.7 ± 14.9 h and 73.8 ± 11.3 h, respectively. Inhalation of B. pseudomallei within 1 μm or 12 μm particle aerosols resulted in a median lethal dose (MLD) of 4 and 12 cfu, respectively. The 12 μm particle inhalational infection was characterized by a marked involvement of the nasal mucosa and extension of bacterial colonization and inflammatory lesions from the olfactory epithelium through the olfactory nerves (or tracts) to the olfactory bulb (100%), culminating in abscessation of the brain (33%). Initial involvement of the upper respiratory tract lymphoid tissues (nasal-associated lymphoid tissue (NALT) and cervical lymph nodes) was observed in both the 1 and 12 μm particle inhalational infections (80–85%). Necrotising alveolitis and bronchiolitis were evident in both inhalational infections, however, lung pathology was greater after inhalation of the 1 μm particle aerosol with pronounced involvement of the mediastinal lymph node (50%). Terminal disease was characterized by bacteraemia in both inhalational infections with dissemination to the spleen, liver, kidneys, and thymus. Treatment with co-trimoxazole was more effective than treatment with doxycycline irrespective of the size of the particles inhaled. Doxycycline was more effective against the 12 μm particle inhalational infection as evidenced by increased time to death. However, both treatment regimes exhibited significant relapse when therapy was discontinued with massive enlargement and abscessation of the lungs, spleen, and cervical lymph nodes observed.